EVALUATION OF THE CONTRIBUTION OF THE REGIONAL GOVERNMENT INFORMATION SYSTEM (SIPD) IN BANGAH VILLAGE, GEDANGAN DISTRICT, SIDOARJO REGENCY - Novitasari, Amelia Vega; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the contribution of the Regional Information System (SIPD) in Bangah Village, Gedangan District, Sidoarjo Regency. Method: The method applied is a descriptive qualitative research approach. Results: SIPD was implemented in Bangah Village, Gedangan District, Sidoarjo Regency in 2023. Various parties are involved in its implementation, including the sub-district head (camat), who holds the highest authority in management and administration, along with the implementation staff under him who possess expertise in information technology management. The government provides input in the form of system management by the sub-district head and implementing staff or employees. In addition, a Musrenbang system (development planning meeting) is also held. The Regional Information System (SIPD), which consists of a database divided into eight (8) data groups, is an effort by the regional government to enhance the role of data and information sourced from all Regional Work Units (SKPD) in Sidoarjo Regency for development planning processes. However, the database in Sidoarjo Regency has not yet been evenly distributed across various villages, including Bangah Village, where public access to data information in SIPD remains suboptimal. Novelty: The distinction between this study and previous research lies in its greater focus on how the contribution of the regional government’s information system is assessed using the CIPP evaluation model theory.